Pemanfaatan Pekarangan Rumah dalam Rangka Kemandirian Ketahanan Pangan di Era Pandemik COVID-19 - Iseu Anggraeni (LPPM UNINUS, 2022)
The purpose of this activity is to find out the use of yard land for self-reliance in terms of fulfilling family food during the COVID-19 pandemic. The COVID-19 pandemic has had a broad impact on various sectors, including the agricultural sector which has an impact on food availability and distribution. Strengthening local food productivity at the household or community scale is the key to anticipating food scarcity. This activity uses discussion and socialization methods, field surveys as well as exercises and practices. Selection of activity participants, namely households that use their yards for gardening activities; resides in Ibun Village, Bandung Regency. The results of the inventory of plants in the yard were found that many had grown various kinds of vegetables such as chilies, tomatoes and green onions. Most people think that gardening activities in their yards help them in meeting their food needs during the COVID-19 pandemic. People think that the consumption of vegetables and other foodstuffs from their own gardens is relatively safer and more economical. In addition, there are enthusiastic residents who are actively processing herbal plants in an effort to increase body resistance.